Selective nanofiber deposition via electrodynamic focusing - Wan Salim, Wan Wardatul Amani; Son, Chulwoo; Ziaie, Babak (IOP Publishing Ltd., 2008)
In this paper, we demonstrate the effect of electrodynamic focusing through a gold-coated PDMS shadow mask on the selective deposition of electrospun nanofibers. Under a suitable applied voltage, the PDMS mask repels the fibers from its surface while simultaneously forcing them into micron-sized holes and onto a collecting substrate. The presented technique is simple and can be used to produce lithographic-scale nanofiber deposition using a wide range of materials.